Multiproxy study of a wet depositional environment in Pereira, central Andes (2018)
The description of past environments pervades the test of time through the "finger prints" left by organisms in the past. These markers can range from the macro to the micro scale; from a big fossil like dinosaur bones to molecules. Biomarkers are a group of molecular biological fossils that allow paleoenvironmental and paleoclimatical reconstructions. This study describes a biomarker study performed in an outcrop situated in Pereira, Colombia(4°43', 060 N; 75°37', 040 W). The outcrop expands for 8 m but the present study focuses on the bottom 5.15 m of the stratigraphic column. The column is a volcanodetritic fan with several ash layers interspersed by sandy deposits. We observe terrigenous plants population over 75% along the outcrop with important episodes of bacterial and macrophytes increases that suggest an input of water as a consequence of climate complexity in this area. Also, the methanogenic processes are mostly related with the variation